Efektivitas Pendidikan Gizi dengan Media Kartu Edukasi Gizi terhadap Peningkatan Pengetahuan, Sikap dan Perilaku Makanan Jajanan Anak Sekolah Dasar - Witri Priawantiputri; Mamat Rahmat; Asep Iwan Purnawan (Politeknik Kesehatan Tanjung Karang, 2019)
The safety of snack food for elementary school children is a major problem that becomes public attention. Nutrition education using attractive media such as nutrition cards is needed to improve children's knowledge and behavior on consuming a healthy snack. The purpose of this study was to identify the effectiveness of nutrition education using nutrition cards on increasing knowledge, attitudes, and behavior of Elementary School Children. A quasi-experimental of two groups with pretest and posttest study was conducted among 66 elementary school children in Elementary School 154 Citepus Bandung. The intervention was carried out for 3 weeks. The treatment group was given nutrition education using nutrition cards, meanwhile, the control group was given a lecture using powerpoint. Data analysis used in this study was the Wilcoxon test. To identify the effectiveness of increasing knowledge, attitudes, and behavior between the two groups, the Mann Whitney test was used. The results showed an increase in the score of students' knowledge, attitudes, and behavior after intervention among the treatment and control group (p-value<0,05). Based on the Mann-Whitney test, there was a significant difference between the increase in students' knowledge scores in the treatment group and the control group, the knowledge score in the treatment group was higher than the control group (p-value<0,05). The increase in students' attitudes and behavior scores between the treatment group and the control group was statistically no significant difference (p-value>0,05). Nutrition cards can be used as attractive media to increase children's knowledge and attitude toward choosing healthy snacks.